2021
DOI: 10.1097/phh.0000000000001393
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Public Health Workforce Informatics Competencies: A Study of 3 District Health Departments in Georgia

Abstract: Context: Despite the increased recognition of the importance of having informatics-competent public health professionals, the competency level of the public health workforce in public health informatics (PHI) has not been examined extensively in the literature. Objective: The purpose of this study was to assess public health workforce informatics competencies in select Georgia health districts and determine the correlates of PHI proficiency. Methods: This study is based on a cross-sectional quantitative study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Table 3 describes the 12 publications included in this review, all by authors in North America. [34][35][36][37][38][39][40][41][42][43][44][45] Eleven out of twelve publications were written by first authors in the United States, [34,[36][37][38][39][40][41][42][43][44][45] (5/12) were published between 2010-2015[36, 39, 40, 42, 45] and (6/12) were commentaries or perspectives. [35,37,38,[42][43][44] Of these, the 4 studies included in the quality appraisal showed variable quality with 3 being observational studies (Multimedia Appendix 2).…”
Section: Characteristics Of Included Publicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 3 describes the 12 publications included in this review, all by authors in North America. [34][35][36][37][38][39][40][41][42][43][44][45] Eleven out of twelve publications were written by first authors in the United States, [34,[36][37][38][39][40][41][42][43][44][45] (5/12) were published between 2010-2015[36, 39, 40, 42, 45] and (6/12) were commentaries or perspectives. [35,37,38,[42][43][44] Of these, the 4 studies included in the quality appraisal showed variable quality with 3 being observational studies (Multimedia Appendix 2).…”
Section: Characteristics Of Included Publicationsmentioning
confidence: 99%
“…Practice competencies were most described in relation to public health research (10 articles), [34-42, 44, 45] epidemiology and surveillance (9 articles), [34-38, 40, 41, 44, 45] risk assessment (3 articles), [34,35,40] and health promotion (3 articles) [40,43,45] (Table 3).…”
Section: Domains Of Public Health Relevant To Digital Technologiesmentioning
confidence: 99%
See 3 more Smart Citations